Integrasi Wakaf dengan Instrumen Keuangan Syariah melalui CWLS di BSI Bojonegoro - Shofa Robbani; Nur Azwajum Muthoharoh; Miftakhun Nasikhatin Ni’amah; Siti Maulidiana; Syahrul Idzom Mahendra; Akmal Bayu Aji (STIS DAFA MATARAM, 2025)
The purpose of this study is to examine the implementation of sukuk related to cash waqf at BSI Bojonegoro Branch. The main focus is to understand how waqf is integrated with CWLS, see the supporting and inhibiting factors, and assess its potential and impact on regional economic and social development. The qualitative descriptive method, and using primary data with interviews and secondary data from literature reviews. The results obtained indicate that the CWLS mechanism at BSI Bojonegoro has followed national guidelines, supported by regulations, BSI's commitment, and public awareness of waqf. However, there are several obstacles such as low community literacy, low minimum wages, and the need to increase trust in local communities. Although the real impact of CWLS in Bojonegoro has not been widely felt, there is significant potential to raise funds for social and economic programs. The contribution of this study provides a specific case study of CWLS at the local level, which is expected to be a reference for BSI and other stakeholders in developing adaptive strategies. This aims to ensure that the benefits of productive waqf can be felt more widely and more clearly in empowering the community's economy.